The effects of ENSO and the North American monsoon on mast seeding in two Rocky Mountain conifer species. (6th December 2021) - Wion, Andreas P.; Pearse, Ian S.; Rodman, Kyle C.; Veblen, Thomas T.; Redmond, Miranda D.
Abstract : We aimed to disentangle the patterns of synchronous and variable cone production (i.e. masting) and its relationship to climate in two conifer species native to dry forests of western North America. We used cone abscission scars to reconstruct ca 15 years of recent cone production in Pinus edulis and Pinus ponderosa, and used redundancy analysis to relate time series of annual cone production to climate indices describing the North American monsoon and the El Niño Southern Oscillation (ENSO). We show that the sensitivity to climate and resulting synchrony in cone production varies substantially between species. Cone production among populations of P. edulis was much more spatially synchronous and more closely related to large-scale modes of climate variability than among populations of P. ponderosa . Large-scale synchrony in P. edulis cone production was associated with the North American monsoon and we identified a dipole pattern of regional cone production associated with ENSO phase. In P. ponderosa, these climate indices were not strongly associated with cone production, resulting in asynchronous masting patterns among populations. This study helps frame our understanding of mast seeding as a life-history strategy and has implications for our ability to forecast mast years in these species. This article is part of the theme issue 'The ecology and evolution of synchronized seed production in plants'.